Child and parent reports of children's depressive symptoms in relation to children's weight loss response in family‐based obesity treatment. Issue 7 (21st January 2019) - Conlon, Rachel P. Kolko; Hurst, Kelly T.; Hayes, Jacqueline F.; Balantekin, Katherine N.; Stein, Richard I.; Saelens, Brian E.; Brown, Mackenzie L.; Sheinbein, Daniel H.; Welch, R. Robinson; Perri, Michael G.; Schechtman, Kenneth B.; Epstein, Leonard H.; et al.
Summary: Background: Studies of the association between children's depressive symptoms and obesity treatment response show mixed results. Different measurement may contribute to the inconsistent findings, as children's depressive symptoms are often based on parent‐report about their child rather than child self‐report. Objectives: We assessed both child‐ and parent‐report of child depressive symptoms as predictors of children's obesity treatment response. Methods: Children with overweight/obesity (body mass index [BMI] ≥ 85th percentile; N = 181) and their parents reported on children's depressive symptoms prior to family‐based behavioral weight loss treatment. Results: Child percent overweight reduction from baseline to post‐treatment was not predicted by child self‐reported depressive symptoms or parent‐report of child symptoms ( P > 0.80), but was significantly predicted by the interaction between child self‐report and parent‐report on child ( β = 0.14, P = 0.05). In analyses using clinical cutoffs, amongst children with high self‐reported symptoms, those whose parents reported low child depressive symptoms had greater reduction in percent overweight ( t = 2.67, P = 0.008), whereas amongst children with low self‐reported symptoms, parent ratings were not associated with treatment outcome. Conclusions: Including both child self‐report and parent‐report of child depressive symptoms may inform obesity care. Research is needed to examine differences amongst child and parent depressive symptom reports and strategies to address symptoms and optimize pediatric obesity treatment.